Lipofundin 20% induces hepatic lipid peroxidation in New Zealand white rabbits - Livan Delgado R (Revista MVZ Córdoba, 2012)
Objective. The aim of the present work was to evaluate the effects of Lipofundin 20% on lipid peroxidation markers in the liver of New Zealand white rabbits. Materials and methods. The animals were treated with an intravenous injection (2 ml/kg) of the lipid emulsion during 8 days through the marginal ear vein. At the end of the experiment some lipid peroxidation parameters and lipid profile were tested through spectrophotography. Results. Lipofundin was found to induce a significant (p<0.05) increase of malondialdehyde, total hydroperoxides, and peroxidation potential. Also, high levels of total cholesterol, triglycerides, LDL - cholesterol and HDL-cholesterol were observed in treated animals compared with the control group (p<0.05). Conclusions. Data proved that Lipofundin induces hepatic lipid peroxidation in rabbits, mainly through a mechanism which involves an induction of hyperlipidemia.